CGIAR Research Program On Water, Land and Ecosystems: Full Proposal 2017-2022 (Updated July 31, 2016) - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2017)
The CGIAR Research Program on Water, Land and Ecosystem Phase 2 proposal provides a comprehensive overview of the proposed program of work. WLE's mission is mission is to provide the evidence base and solutions to help decision makers scale up sustainable water, land and ecosystem management innovations and investments in agricultural landscapes that reduce risks and increase the resilience of women and men in developing countries. It achieves this through a focus on increasing productivity and identifying synergies and managing trade-offs among sectors. WLE supports implementation of multiple Sustainable Development Goals (SDGs). WLE will complement research on specific commodities and value chains by focusing on solutions and innovations to transform both agro- ecosystems and the institutions that manage them. This is achieved in part by clear and agreed linkages with selected AFS CRPs, coordinated through the reformulated ESA flagship. Drawing on the solutions and approaches that have emerged from the first phase, WLE aims to support communities, policymakers, investors and the private sector to make informed decisions on planning and implementing development efforts that impact landscapes. This second phase includes six particularly notable features that complement other CRPs within the CGIAR portfolio. These are: 1) a focus on sustainability and social equality, especially with reference to women and youth to deliver on the newly adopted SDGs; 2) an increased emphasis on restoration of degraded soils and landscapes; 3) building resilience within agri-food systems, particularly in Africa and South Asia through improved water management; 4) addressing the increasing influence of urbanization on rural landscapes and agro-ecosystems; 5) reducing risk and uncertainty for agricultural systems; and 6) finding the right levers for change in the complex environment of Natural Resources Management, including in the CGIAR target countries.